Validation of neutron emission and neutron energy spectrum calculations on a Mega Ampere Spherical Tokamak with directional relativistic spectrum simulator. (4th December 2020) - Sperduti, A; Klimek, I; Conroy, S; Cecconello, M; Gorelenkova, M; Snicker, A
Abstract: The recently developed directional relativistic spectrum simulator (DRESS) code has been validated for the first time against numerical calculations and experimental measurements performed on the Mega Ampere Spherical Tokamak . In this validation, the neutron emissivities and rates computed by DRESS are benchmarked against TRANSP/NUBEAM predictions while the neutron energy spectra provided by DRESS taking as input TRANSP/NUBEAM and ASCOT/BBNBI in Gyro-Orbit mode fast ion distributions are validated against proton pulse height spectra measured by the neutron flux monitor. Excellent agreement was found between DRESS and TRANSP/NUBEAM predictions of local and total neutron emission.